2022
DOI: 10.1002/hep4.2106
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fingers and homeoboxes 2 is required for diethylnitrosamine‐induced liver tumor formation in C57BL/6 mice

Abstract: Liver cancer, comprised primarily of hepatocellular carcinoma (HCC), is the third leading cause of cancer deaths worldwide and increasing in Western countries. We previously identified the transcription factor zinc fingers and homeoboxes 2 (Zhx2) as a regulator of hepatic gene expression, and many Zhx2 target genes are dysregulated in HCC. Here, we investigate HCC in Zhx2‐deficient mice using the diethylnitrosamine (DEN)–induced liver tumor model. Our study using whole‐body Zhx2 knockout (Zhx2KO) mice revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…These increased values show the beginning of HCC in addition to liver damage. This result is in line with earlier research [ 39 , 40 ]. Notably, the Streptomyces sp.…”
Section: Discussionsupporting
confidence: 94%
“…These increased values show the beginning of HCC in addition to liver damage. This result is in line with earlier research [ 39 , 40 ]. Notably, the Streptomyces sp.…”
Section: Discussionsupporting
confidence: 94%
“…Compared to BALB/c mice, Zhx2 hypo/hypo BALB/cJ mice developed less severe heart, liver and kidney injury and lower mortality, whereas the extent of glomerular injury was similar. The disparity between glomerular and other forms of injury is possibly related the predominantly cell membrane localization of ZHX proteins in podocytes (27,40,41), and largely nuclear expression in the heart (42), liver (43) and kidney tubular cells (27), although the use of low confidence and polyreactive antibodies to stain human tissue in a key resource (42) These studies showcase the concept of synergy between different cytokines, compartments and signaling pathways in disease pathogenesis. Cytokine depletion regimens described in this study also affect this synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, latest studies reported that ZHX2 functions as an oncogene in ccRCC (13,14) and TNBC (16). Likewise, Jiang et al reported that the whole-body knockout of Zhx2 results in reduced liver tumors in diethylnitrosamine (DEN)-induced HCC mice (52). Therefore, ZHX2 is abnormally expressed in multiple tumors and plays different roles, either acting as a tumor suppressor or oncogene in a context-dependent manner (Figure 2).…”
Section: Zhx2 In Cancer-a Contextdependent Tumor Repressor or Driver?mentioning
confidence: 98%
“…Jiang et al recently showed that whole body Zhx2 knockout (Zhx2 KO ) leads to dramatically reduced liver cancer in DEN-induced HCC mouse model, indicating the oncogenic role of ZHX2 in DENinduced liver tumor model (52). Interestingly, compared with Zhx2 KO mice, DEN induces more tumors in liver-specific Zhx2 knock-out mice (Zhx2 Dliv ) (52). These data suggest that ZHX2 expression in non-parenchymal cells plays a critical role in liver carcinogenesis.…”
Section: Zhx2 As a Tumor Suppressor In Hcc And Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation